A Bibliometric-Statistical Review of Organic Residues as Cementitious Building Materials - Sergio Yanez; Constanza Márquez; Benjamín Valenzuela; Cristina Alejandra Villamar-Ayala (Buildings, 2022)
Climate deterioration and environmental pollution has been widely studied by a wide scientific community. The effects of the ecosystem deterioration impacts directly to human activities. In this scenario, the building industry has increased the pressure on proposing new materials to replace the cementicious component and natural resources (water, sand, gravel, and limestone) on mortar and concrete to reverse this trend. To this end, organic residues can offer opportunities as an available alternative for construction applications. Therefore, this paper aims to broaden the scope of research in this field by investigating the potential use of organic residues as cementicious building material based on bibliometric-statistical analysis using scientific information. A preliminary bibliometric analysis using VOSviewer was carried out to define the keywords co-ocurrence from Scopus database. Type of organic material, constructive use, and its properties (physicochemical, mechanical, and thermal) were extracted from scientific publications. Then, a systematic analysis criteria was defined to limit the scope of the study. Finally, statistical variance analysis and multiple correlation for identifying constructive application were applied. From the co-ocurrence analysis of keywords, we determined that 54% of the selected scientific publications were closely related to the scope of this study. State-of-the-art study established that related researches grew exponentially at a rate of about <semantics>30%</semantics>/year. Moreover, scientific publications reported the use of a wide variety of organic residues, such as wheat, paper, hemp, rice, wood, molluscs, olive, coconut, among others. Mainly, agricultural residues (<semantics>82%</semantics>) with building applications related to structural concrete, mortar, bricks, and blocks, had been evaluated. Physicochemical properties from organic residues (extractives content, lignin content, and density) were correlated to mechanical (compressive, flexural and tensile strength) and thermal properties (thermal conductivity). The identification of the physicochemical properties of the organic residues allow us to predict the mechanical and thermal behavior of the material with residues. In summary, agricultural residues are the most promising organic building material due to their abundance and lignin content, exhibiting better mechanic and thermal properties than any other organic residues.